Efektivitas Model Pembelajaran Problem Based Learning Berbantuan LKS Terhadap Kemampuan Berpikir Kritis Fisika Siswa SMAN 1 Lingsar Tahun Ajaran 2016/2017 - Islamiah, Andi Fatimatul; Rahayu, Satutik; Verawati, Ni Nyoman Sri Putu (Lensa : Jurnal Kependidikan Fisika, 2018)
[Title: The Effect of Thinking Aloud Pair Problem Solving Learning Model Toward Student Physics Science Learning Outcomes]. This research aims to know the effectiveness of the learning problem based learning model assisted work sheet for the critical thinking ability of physics students of grade X SMAN 1 Lingsar inacademics year 2016/2017. This was an experiments research that using design research Posttest-Only Control group Design. The population in this research were the whole grade X SMA Negeri 1 Lingsar in academics year 2016/2017. Sampling taken with using cluster random sampling technique with the students of class X. MIA. A as experiments class and grade X. MIA. D as controls class. Research hypothesis was analysis with the t-test for one party (the party right). Based on the hypothesis test results obtained tcount> ttable at significance level of 5%, then it can be inferred that the model of learning problem based learning assisted work sheet effective for critical thinking ability of physics students SMAN 1 Lingsar.